INSULIN SHOCK DAN HUBUNGANNYA DENGAN METABOLISME TUBUH - HAVIZ, M. (Sainstek : Jurnal Sains dan Teknologi, 2012)
The presence of insulin in the human body is very necessary. Insulin has an effect on the metabolism of the body. There are significant physiological changes in the body when insulin deficiency or excess. This paper to discusses about the relationship insulin with metabolism of the body through a literature review and mini research. Is the body condition if the excess or deficiency of insulin? The above questions will be answered through the review authors in this article. Weitz report (2007) about the experience of observation insulin shock therapy in patients with schizophrenia. Then, followed by reports of a mini research that have been conducted on insulin shock in fish. Based on the discussion of the results and some conclusions can be drawn (1) Glucose levels in plasma and liver is strongly influenced by the presence of insulin and glucagon, (2) lack or excess of insulin as a hormone and glucose as substrate will lead to abnormality in the body's physiological.Key words: insulin shock, metabolism